Epileptic seizures in children with congenital Zika virus syndrome - Lucas Victor Alves; Danielle Di Cavalcanti Sousa Cruz; Ana Maria Campos van der Linden; Ana Rodrigues Falbo; Maria Júlia Gonçalves de Mello; Camila Esteves Paredes; Germanna Virginya Cavalcanti Silva; José Natal Figueiroa; Patrícia Gomes de Matos Bezerra
Abstract Objectives: to describe preliminary data referred to epileptic seizures and the probability of occurring these epileptic seizures in the infants' first months of life with congenital Zika virus (ZIKV) syndrome. Methods: concurrent cohort study including newborns and infants with congenital Zika virus syndrome attended at the specialized outpatient clinic at IMIP, Recife, Pernambuco, from October 2015 to May 2016. Results: data on 106 infants were analyzed with confirmed or suspected association to ZIKV infection. Forty children (38.7%) presented an epileptic seizure, classified at 43.3% of the cases as being spasms, 22.7% as generalized tonic seizures, 20.5% as partial and 4.5% other types of seizures. The median of days until the first report on the occurrence of epileptic seizure was 192 days of life. Conclusions: children with congenital Zika virus syndrome presented a high incidence of epileptic seizures before the end of the first semester of life, and spasm was the epileptic seizure mostly observed.